THE STUDY OF SPORTS PERFORMANCE AND EMOTIONAL INTELLIGENCE IN KABADDI STATE LEVEL PLAYERS - Petkar, Vicky Tulshiram (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The purpose of the study was to find out the relationship between Emotional Intelligence and sports performance in Kabaddi. The subject for the study were 50 Male kabaddi State level players of Maharashstra. The data pertaining to emotional intelligence was collected by administering the Emotional Intelligence Questionnaire in Sports (EIQS) Questionnaire which contains 36 statements and also it has six-variables, self-confidence, self-awareness, self-control, motivation, empathy, social competence which has six statements under each six variables. The questionnaire is a standardized questionnaire developed by Sharma and Tiwari with Crombha alpha reliability of 0.95. The data pertaining to sport performance was obtained by administering sports performance evaluation test which consist of two statements and was found to be highly reliable. The raw data obtained by administering emotional intelligence questionnaire in sports and performance evaluation test the data was analyzed statistically by using pearson’s product moment co-relation (r).